Enantioselective syntheses of (E)-γ, δ-disubstituted homoallylic alcohols via BF3·OEt2-catalyzed aldehyde allylboration and analysis of the origin of E-selectivity: A1, 2 allylic strain vs. syn-pentane interaction. Issue 31 (2nd August 2019) - Liu, Jiaming; Gao, Shang; Chen, Ming
Abstract: Enantioselective allylboration of aldehydes with α-substituted β-methyl allylboronate was reported. By using BF3 ·OEt2 as the catalyst, γ, δ-disubstituted homoallylic alcohols were obtained in good yields with high E -selectivities and enantioselectivities. Transition state analysis revealed that the disfavored transition state suffers from a syn -pentane interaction between the BF3 catalyst and axially oriented α-substituent of the allylboron reagent. Such a syn -pentane interaction is severe enough to overcome the A 1, 2 allylic strain between the β-methyl group and the α-substituent of the boron reagent that is present in the favored competing transition state. Consequently, the reaction proceeded with equatorial placement of the α-substituent to furnish γ-methyl substituted homoallylic alcohols with high E -selectivity. Graphical abstract: Image 1